2016
DOI: 10.5849/forsci.15-109
|View full text |Cite
|
Sign up to set email alerts
|

Multienvironment Evaluation ofPinus pinasterProvenances: Evidence of Genetic Trade-Offs between Adaptation to Optimal Conditions and Resistance to the Maritime Pine Bast Scale (Matsucoccus feytaudi)

Abstract: per la ricerca in agricoltura e l'analisi dell'economia agraria, Research Unit for Climatology and Meteorology applied to Agriculture (CREA-CMA), via della Navicella 2-4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Concerning intraspecific variation in relation to resistance against pathogens, some maritime pine provenances from the Western Mediterranean were reported to be resistant to the scale insect Matsucoccus feytaudi Duc. (Di Matteo and Voltas 2016). Genetic intrapopulation variation was also observed in P. pinaster resistance to Hylobius abietis L., Dioryctria sylvestrella Ratz., and Fusarium circinatum Nirenberg and O'Donnell (Kleinhentz et al 1998;Zas et al 2005;Vivas et al 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Concerning intraspecific variation in relation to resistance against pathogens, some maritime pine provenances from the Western Mediterranean were reported to be resistant to the scale insect Matsucoccus feytaudi Duc. (Di Matteo and Voltas 2016). Genetic intrapopulation variation was also observed in P. pinaster resistance to Hylobius abietis L., Dioryctria sylvestrella Ratz., and Fusarium circinatum Nirenberg and O'Donnell (Kleinhentz et al 1998;Zas et al 2005;Vivas et al 2012).…”
Section: Introductionmentioning
confidence: 87%
“…Judging from this model, no strong tradeoffs occurred between growth and reproduction in P. pinaster from Central Spain, so that phenotypic selection of those trees that have larger cone production as seed parents should not forfeit future stand growth in this region. However, trade-offs with other uses of photosynthates such as for defensive chemicals or structures (studied by Moreira et al, 2015or Di Matteo & Voltas, 2016 should be also considered. Our model also points to silvicultural actions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Defenses structures (i.e, resin) require a sufficiently large and permanent resource allocation that tree growth is reduced more on poor sites than on high productivity sites (Ferrenberg et al, 2015). P. pinaster genetic variability is therefore related to differential aboveground resource allocation and resistance to pest attacks (Di Matteo & Voltas, 2016). In this regard, (Moreira et al, 2015) observed wide intra-specific genetic variation in P. pinaster with regard to resource allocation to inducible defenses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, and although the plantations were installed mainly at low-quality sites, the characteristics of these soils were strongly modified by the soil preparation work, so, the growth responses to climatic stress may be tightly conditioned by local site conditions [58]. All these factors may produce a loss of vigor in individual trees, and thus an increased vulnerability to drought events and other stress factors such as pests [59,60]. In this area, extensive tree damage has been also associated also with the Maritime Pine Bast Scale (Matsucoccus feytaudi; R.M.…”
Section: Climate-and Drought-growth Relationships In Planted and Natumentioning
confidence: 99%